gasket

The gasket design with a resin seal made from a polar olefin monomer and polyrotaxane combination addresses seal failures by maintaining sealing performance through deformation, enhancing vertical peelability and reducing debris, thus preventing seal openings.

JP7620179B2Active Publication Date: 2025-01-23NIPPON GASKET CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020108251
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-23
Publication Date
2025-01-23
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

Conventional gaskets with resin sealing parts fail to maintain sealing performance when subjected to stress in the direction of separation between mating members, leading to seal failures due to opening.

Method used

A gasket design incorporating a resin seal portion made from a combination of a first polymer material containing a polar olefin monomer and a second polymer material of polyrotaxane, with the second polymer material added at a ratio of less than 50%, allowing the seal to deform and follow the mating member even when separated.

Benefits of technology

The gasket maintains sealing performance by deforming beyond its original molded height, preventing seal failures and ensuring effective sealing even when the mating members separate, with improved vertical peelability and reduced debris formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620179000003
    Figure 0007620179000003
  • Figure 0007620179000004
    Figure 0007620179000004
  • Figure 0007620179000005
    Figure 0007620179000005
Patent Text Reader

Abstract

To provide a gasket 1 that can properly deal with the opening due to separation of a mating member from the gasket.SOLUTION: This invention relates to a gasket 1 that is held between a member and a member provided with a passage, an opening hole 3 to be dug at the position of the passage and a resin seal part 5 provided so as to surround the opening hole 3. The seal part 5 includes a first polymer material including a constitutional unit of a polar olefin monomer, and a second polymer material composed of a polyrotaxane having a chain molecule penetrating a plurality of cyclic molecules. The first polymer material is blended with the second polymer material at a rate of less than 50%.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gasket, and more particularly to a gasket having a resin sealing portion provided so as to surround an opening provided in a substrate. [Background technology]

[0002] Conventionally, gaskets have been known that are sandwiched between components having a passage formed therein to seal them. Known examples of such gaskets include a gasket that has a resin sealing portion made of vulcanized rubber or the like that surrounds an opening provided in a substrate (Patent Documents 1 to 4). By sandwiching a gasket having such a resin sealing portion between the above-mentioned members, the sealing portion is compressed to perform sealing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 2767862 [Patent Document 2] Japanese Patent Application Publication No. 61-043552 [Patent Document 3] Patent No. 3467196 [Patent Document 4] Patent No. 4069344 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, when vibration acts on the member that holds the gasket, stress acts in a compression direction in part of the contact area between the member and the gasket, and stress acts in the direction separating the gasket from the member in other parts. In the case of a gasket having a sealing portion made of vulcanized rubber or the like as described in Patent Document 1 and the like, when stress acts in the compression direction, the gasket can absorb the stress by elastically deforming and maintain its sealing performance. However, when stress acts in the separation direction, the seal portion made of fluororubber can only restore to the molded height at the time of manufacture, so if the mating component separates further, the seal portion cannot follow and separates from the mating component, resulting in a so-called open mouth condition and causing a poor seal. In view of the above problems, the present invention provides a gasket that can effectively deal with the gap caused by separation between the mating member and the gasket. [Means for solving the problem]

[0005] That is, the gasket according to the invention of claim 1 is a gasket having a base plate sandwiched between members and having an opening formed therein, and a resin seal portion provided so as to surround the opening of the base plate, The sealing portion includes a first polymer material including a structural unit of a polar olefin monomer represented by the following chemical formula 1, and a second polymer material including a polyrotaxane having a chain molecule passing through a plurality of cyclic molecules, (Chemical formula 1)CH2=CH-R 2 -Z(R 1 ) n (wherein Z is a heteroatom selected from the group consisting of nitrogen, oxygen, phosphorus, sulfur, and selenium; R 1 is a substituted or unsubstituted hydrocarbyl group having 1 to 30 carbon atoms, R 2 is a substituted or unsubstituted hydrocarbylene group having 2 to 20 carbon atoms. The second polymer material is added to the first polymer material at a ratio of less than 50%. Effect of the Invention

[0006] As a result of the experiments described below, it was confirmed that the gasket according to the above-mentioned invention has the vertical peelability to deform beyond its original molded height and follow the mating component even when the mating component separates, and has good sealing properties against the opening. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a plan view of a gasket according to an embodiment of the present invention; [Diagram 2] Cross-sectional view of part II-II of the above gasket [Diagram 3] FIG. 1 is a diagram illustrating the structure of a first polymer material. [Figure 4] FIG. 1 is a diagram illustrating the structure of a second polymer material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The illustrated embodiment will now be described. FIG. 1 shows a plan view of a gasket 1 according to this embodiment, and FIG. 2 shows a cross-sectional view of the II-II portion in FIG. The gasket 1 of this embodiment is adapted to be sandwiched between two components (not shown), for example, between the head and block that make up an automobile engine, to seal the gas flowing through the passages formed therebetween. The gasket 1 is composed of a metal substrate 2, an opening hole 3 drilled in the metal substrate 2 to match the position of the passage formed in the mating member, a plurality of bolt holes 4 drilled in positions adjacent to the opening hole 3, and a resin seal portion 5 formed on both the upper and lower surfaces of the metal substrate 2 and surrounding the opening hole 3. The seal portion 5 has a cross-sectional shape that is approximately semicircular, and the height and width of the seal portion 5 can be appropriately changed depending on the manner in which the gasket 1 is used. In addition, the gasket 1 of this embodiment may be formed from multiple metal substrates 2, and a bead shape consisting of a convex shape surrounding the opening may be provided at a position adjacent to the inner or outer periphery of the sealing portion 5.

[0009] The gasket 1 in this embodiment, in which a resin seal portion 5 is formed around an opening 3, is conventionally known as described in the above-mentioned Patent Document 1. Here, in the case where the sealing portion 5 is made of fluororubber as in Patent Document 1, when the gasket 1 is sandwiched between the counter members, the sealing portion 5 is elastically compressed and comes into close contact with the counter member, thereby sealing the gas flowing through the passage. However, when the mating members are tilted relative to each other due to engine vibration or the like, some of the contacting portions of the gasket 1 tend to separate due to the tilt. If the amount of separation is small and within a range in which the seal portion 5 of the gasket 1 can recover from the elastically deformed state and maintain contact with the mating member, the sealed state can be maintained. However, if the mating member becomes too far away from the gasket 1 and becomes farther away than the height at which the seal portion 5 was formed, the seal portion 5 will no longer be able to maintain close contact with the mating member. This causes a portion of the gasket to separate from the mating member, leaving an opening, which allows the gas to leak out and results in poor sealing. To address this problem, the gasket 1 of this embodiment is designed so that even if the distance between the gasket and the mating member increases, the sealing portion 5 follows this and prevents poor sealing due to opening.

[0010] The sealing portion 5 will now be described. The sealing portion 5 is composed of a resin containing a first polymer material made of a polar olefin monomer represented by the following chemical formula 1, and a second polymer material made of a polyrotaxane in which a chain molecule passes through multiple cyclic molecules. (Chem.1)CH2=CH-R 2 -Z(R 1 ) n (wherein Z is a heteroatom selected from the group consisting of nitrogen, oxygen, phosphorus, sulfur, and selenium; R 1 is a substituted or unsubstituted hydrocarbyl group having 1 to 30 carbon atoms, R 2 is a substituted or unsubstituted hydrocarbylene group having 2 to 20 carbon atoms.

[0011] The first polymer material represented by the above chemical formula 1 is an ethylene-anisylpropylene copolymer, and as shown in FIG. 3, has a structure in which alternating units 11 of anisylpropylene and ethylene exist as soft components, together with units 12 of ethylene-ethylene chains (shown by dotted lines in the figure) as hard components. The first polymer material having the above-mentioned configuration exhibits elastomeric properties because the ethylene-ethylene chain units 12 function as crosslinking points, and also has the property of repairing itself through intermolecular interactions to balance the disorder caused by breakage. In addition, the R group of the anisyl group can be substituted in various ways. For example, by replacing it with a bulky substituent such as a t-Bu group, it is possible to control the thermal properties of the polymer so that it becomes a hard plastic at room temperature and exhibits elastomeric properties when heated.

[0012] The first polymer material may be a copolymer containing the structural unit of the polar olefin monomer represented by the above chemical formula 1, and further containing the structural unit of at least one non-polar olefin monomer (eg, ethylene). The first polymer material may also include an alternating sequence of structural units of the at least one polar olefin monomer represented by Chemical Formula 1 and structural units of the at least one non-polar olefin monomer, and a polymerization sequence of the at least one non-polar olefin monomer. The ratio of polar olefin structural units to all structural units in the first polymer material may be 20 mol % or more. The number average molecular weight of the first polymer material is 2.0×10 3 or more, and the number average molecular weight is 5.0×10 3 Above 4.0×10 3 The glass transition point is preferably −30° C. or higher and 10° C. or lower.

[0013] The polar olefin monomer may be a polar olefin monomer represented by the following chemical formula 2. (Case 2) TIFF0007620179000001.tif35170 (wherein Z is a heteroatom selected from the group consisting of nitrogen, oxygen, phosphorus, sulfur, and selenium; R 1 is a substituted or unsubstituted hydrocarbyl group having 1 to 30 carbon atoms, n is an integer of 1 or 2 depending on the atomic type of Z, R 3 is a hydrocarbylene group having 1 to 5 carbon atoms, R 4 is a halogen atom, a hydrocarbyl group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an alkylamino group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; R 4 When represents a hydrocarbyl group, they may be bonded to form a condensed ring, and m is an integer of 0 to 4. Examples of the polar olefin monomer of the above chemical formula 2 include substituted 2-allylanisoles (hereinafter referred to as "APs") such as 2-allyl-4-fluoroanisole, 2-allyl-4,5-difluoroanisole, 2-allyl-4-methylanisole, 2-allyl-4-tert-butylanisole, 2-allyl-4-hexylanisole, 2-allyl-4-methoxyanisole, and 3-(2-methoxy-1-naphthyl)-1-propylene. R "); unsubstituted 2-allylanisole (3-(2-anisyl)-1-propylene) (hereinafter also referred to as "AP"); and the like.

[0014] Alternatively, the first polymer material may be a copolymer containing at least a structural unit represented by (III) or (IV) in the following chemical formula 3. (3) TIFF0007620179000002.tif86170 (in the formula, R 1 , R 3 , R 4 , Z, m, and n are the same as those in the above chemical formula 2, and x and y represent the proportion (molar ratio) of each structural unit in the entire sequence of the copolymer, and are positive numbers satisfying x>0, y>0, x>y, and 80%≦x+y≦100% (for example, x is 30 mol% or more, or 40 mol% or more. Also, for example, x+y is 85% or more, 90% or more, 95% or more, or 97% or more). As a specific example, the first polymer material created by the RIKEN Institute used in the following experiment has Z as an oxygen atom and R 1 is a methyl group, n is 1, m is 0, R 3 is a methylene group, x is about 40 mol %, and y is about 60 mol %, and the polymer has a number average molecular weight of about 90,000 and a glass transition point of about -5°C. The first polymer is not limited to the polymer with the above structure, and may be one in which R1 is replaced with a substituent other than a methyl group. In addition, the number average molecular weight is in the range of 50,000 to 400,000, and the glass transition point is in the range of -30°C to 10°C, so that the first polymer can function as a sealing material. Further details of the first polymer material are disclosed in International Publication WO2019 / 177110 and Haobing Wang, Yang Yang, Masayoshi Nishiura, Yuji Higaki, Atsushi Takahara, Zhaomin Hou, "Synthesis of Self-Healing Polymers by Scandium-Catalysed Co-polymerization of Ethylene and Anisylpropylenes", J. Am. Chem. Soc. 2019, 141, 7, 3249-3257.

[0015] As shown in FIG. 4, the second polymer material is composed of a molecular assembly called polyrotaxane, in which multiple cyclic molecules 13 are threaded through chain molecules 14, and cyclodextrin is introduced as the cyclic molecule 13 into polyethylene glycol as the chain molecule 14. In this embodiment, the chain molecule 14 may be the polyethylene glycol, and the chain molecule 14 has a molecular weight of about 10,000 to 40,000. Cyclodextrin as the above-mentioned cyclic molecule 13 is a compound in which glucopyranose units are linked in a ring shape by α-1,4-glucosidic bonds, and since the outside of the cavity of the cyclodextrin is hydrophilic and the inside is hydrophobic, it is known to form an inclusion compound by incorporating hydrophobic molecules into the inside of the cavity. In the second polymer material having the above configuration, the cyclic molecules 13 are capable of moving along the chain molecules 14, and since the cyclodextrin has many hydroxyl groups, these hydroxyl groups act as crosslinking points (dotted line parts in the figure) to crosslink with other sets of cyclic molecules 13, forming a chain structure. The second polymeric material of this example is available as Celmus-Perpolymer SH1300P from Advanced Soft Materials. Details of the second polymer material are disclosed in A. Harada, J. Li, M. Kamachi, Nature 356, 325 (1992).

[0016] In the present embodiment, the resin constituting the seal portion 5 is obtained by adding the second polymer material to the first polymer material at a concentration of less than 50%. If the concentration exceeds 50%, the conformability to the mating material is deteriorated, and there is a risk of an opening occurring. Furthermore, when forming a sealing portion made of the above resin on a metal substrate, it is possible to use toluene or ketones as a solvent to prepare a solution in which the above first polymer material and second polymer material are mixed. The prepared solution is applied to the metal substrate 2 by a method such as screen printing, and then the toluene and ketones in the solution are evaporated, thereby forming the seal portion 5 on the metal substrate 2. In the process of forming the seal portion 5 on the metal substrate 2, a heat treatment for vulcanization is not required.

[0017] The resin constituting the sealing portion 5 is pressed against a required portion of the sealing portion 5 (description will correspond to the actual test content) with a cylindrical jig having a diameter of 5 mm and a load of 80 N for 20 seconds, and then the cylindrical jig is moved upward at a speed of 0.1 mm / s, and the adhesion load acting on the cylindrical jig is 5 N or more. The above-mentioned sticking load indicates the vertical peeling property of the seal portion 5 following the mating member when the gasket 1 and the mating member are separated, and if it is less than 0.1 N, good sealing property is not obtained with respect to the opening.

[0018] The following describes the results of experiments conducted on an invention product using the resin used in the gasket of the present invention, and on comparative products 1 and 2 for comparison with the invention product. The invention uses a resin containing the first polymer material and the second polymer material described in the above examples. Specifically, the first polymer material was made by the RIKEN Institute using the same method and conditions as P2 described in the examples of International Publication WO2019 / 177110, and had an average molecular weight of 90,000 with hydrogen atoms linked to the substituents. As the second polymer material, SeRM Super Polymer SH1300P manufactured by Advanced Materials was used. The first and second polymer materials thus prepared were added to the first polymer material so that the second polymer material had a concentration of 5%, and methyl ethyl ketone was further mixed in as a solvent so that the concentration was 62% of the total weight to create a solution. The prepared solution was applied onto a metal plate by means of screen printing and then left for a predetermined time to volatilize the methyl ethyl ketone in the solution, thereby forming a resin portion on the metal plate. The dimensions of the resin part formed on the metal plate must be at least 25 mm. 2 The area was set to 1 mm and the thickness was set to 1 mm.

[0019] Comparative product 1 was made by using fluororubber instead of the resin portion formed on the metal plate of the above-mentioned inventive product, and the size and thickness of the other resin portions were the same as those of the inventive product. For comparison product 2, instead of the resin part formed on the metal plate of the above-mentioned invention product, the first polymer material used in the above-mentioned example was used, but a resin not containing the second polymer material was used, and the width and thickness of the other resin parts were made to be the same dimensions as the invention product.

[0020] First, as Experiment 1, the following experiment was conducted on the above-mentioned invention product and comparative products 1 and 2. In the experiment, a cylindrical jig made of SUS304 and having a diameter of 5 mm was pressed against the resin part at room temperature with a load of 80 N for 20 seconds, and then the jig was moved vertically upward at a speed of 0.1 mm / s. When the jig was moved upward, the stress acting on the jig from the resin portion was measured as the adhesion load. Thereafter, the jig separated from the resin portion was checked to see whether or not any fragments of the resin portion were attached to the portion in close contact with the resin portion.

[0021] As a result of the experiment using the above-mentioned experimental device, the adhesion load was 13.738N for the inventive product, 0N for comparison product 1, and 9.044N for comparison product 2. First, for comparison product 1, when the jig was removed upward, it returned to its original molded thickness from its compressed deformed state, but did not deform any further and immediately detached from the jig, so the adhesion load was 0 N. In other words, when the fluororubber of Comparative Product 1 is used in the gasket 1 as the sealing portion 5, if the mating member is excessively separated from the gasket 1, sufficient sealing performance cannot be obtained for the opening. In contrast, for the inventive product and comparative product 2, when the jig was separated, the deformation exceeded the original molding height, and vertical peeling property was confirmed, which followed the jig. From this, it is presumed that when the resin of the inventive product or comparative product 2 is used in the gasket 1 as the sealing part 5, sealing property can be maintained even when the mouth is opened. When comparing the product of the invention with comparative product 2, the product of the invention had vertical peelability that was about 1.5 times that of comparative product 2. Therefore, it is presumed that when the resin of the product of the invention is used in a gasket 1 as the sealing portion 5, even better sealing properties can be obtained than with comparative product 2. Next, the contact areas of the jig separated from the invention product and comparison products 1 and 2 were observed. In either case, no fragments or other parts that constituted the resin part were found on the jig.

[0022] In Experiment 2, further experiments were conducted on the invention product and comparative product 2, which exhibited the above-mentioned vertical peelability. In this experiment, as in Experiment 1, a resin portion formed on the surface of the metal plate was applied with a diameter of 11.3 mm (area of ​​100 mm) at room temperature. 2 A cylindrical jig made of SUS304 (equivalent to SUS304 1000 mm²) was pressed against the specimen for 20 seconds at loads of 200N, 400N, 600N, and 800N, and then the cylindrical jig was moved vertically upward at a speed of 0.1 mm / s to measure the adhesion load. In the inventive product, the adhesion loads when loads of 200N to 800N were applied were 45.6N, 47.2N, 48.7N, and 49N, respectively. In contrast, in the comparative product 2, the adhesion loads when loads of 200N to 800N were applied were 32.8N, 35.7N, 36.8N, and 36.5N, respectively. These experimental results also confirm that the product of the invention has better vertical peelability than the comparison product 2, and it is inferred that when the product of the invention is used as gasket 1, better sealing properties can be obtained for the opening compared to when the comparison product 2 is used.

[0023] In this way, the gasket 1 having the sealing portion 5 formed by the resin portion used in the above-mentioned invention can maintain good sealing properties against the opening when the mating member is separated, and also has the following effects. First, when the gasket 1 and the mating member are separated, the resin that constitutes the sealing portion 5 of this embodiment does not remain on the mating member. Therefore, when replacing the gasket 1, it is not necessary to remove fragments of the resin portion from the mating member, which improves maintainability. Secondly, since the sealing portion 5 can conform to the mating component due to its excellent vertical peelability, gaskets 1 that have previously been constructed by stacking multiple metal substrates 2 can be replaced with gaskets 1 with a reduced number of metal substrates 2. In this case, the seal portion 5 may be formed on each metal substrate 2, or on only some of the metal substrates 2. [Explanation of symbols]

[0024] 1 Gasket 2 Metal substrate 3 Opening hole 5 Seal part

Claims

1. A gasket having a base plate sandwiched between two members and having an opening formed therein, and a resin seal portion provided so as to surround the opening of the base plate, The sealing portion includes a first polymer material including a structural unit of a polar olefin monomer represented by the following chemical formula 1, and a second polymer material including a polyrotaxane in which a chain molecule passes through a plurality of cyclic molecules, (Formula 1) CH 2 =CH-R 2 -Z(R 1 ) n (wherein Z is a heteroatom selected from the group consisting of nitrogen, oxygen, phosphorus, sulfur, and selenium; R 1 is a substituted or unsubstituted hydrocarbyl group having 1 to 30 carbon atoms, R 2 is a substituted or unsubstituted hydrocarbylene group having 2 to 20 carbon atoms. A gasket comprising the first polymer material and the second polymer material added in a ratio of less than 50%.

2. 2. The gasket according to claim 1, wherein the polyrotaxane as the second polymer material is a molecular aggregate composed of cyclodextrin as a cyclic molecule and polyethylene glycol as a chain molecule.

3. 3. A gasket as described in claim 1 or 2, characterized in that when a cylindrical jig made of SUS304 having a diameter of 5 mm is pressed against the sealing portion with a load of 80 N for 20 seconds and the cylindrical jig is moved upward at a speed of 0.1 mm / s, the adhesion load acting on the cylindrical jig is 5 N or more.

Citation Information

Patent Citations

  • Composite material and manufacture thereof

    JP1986043552A

  • Gasket for intake manifold

    JP1996247292A

  • Cap liners, closures and gaskets from multi-block polymers

    JP2008545017A

  • Resin reaction product and molding containing the same

    JP2013209460A

  • Seal member

    JP2016058138A